Implications of home conditions and practices in Macabebe for health and science instruction in Grades I and II - Bautista, Policarpio B. 1921- (s.n.], 1962)
The home conditions and practices in Macabebe that may have implications for Health and Science Instruction in the first two grades in school are determined in this study. The details of instruction in Health and Science instruction in Grades I and II are first identified.